1993
DOI: 10.1038/363640a0
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of CHOP to a novel RNA-binding protein in human myxoid liposarcoma

Abstract: Human myxoid liposarcomas contain a characteristic chromosomal translocation, t(12;16)(q13;p11), that is associated with a structural rearrangement of the gene encoding CHOP, a growth arrest and DNA-damage inducible member of the C/EBP family of transcription factors residing on 12q13.1. Using a CHOP-specific complementary probe and antiserum we report here the presence of an abnormal CHOP transcript and protein in these tumours. Cloning of the translocation-associated CHOP gene product revealed a fusion betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
649
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 826 publications
(659 citation statements)
references
References 17 publications
8
649
0
2
Order By: Relevance
“…5 Myxoid liposarcoma represents 20-30% of all liposarcomas, mostly occurs in young adults, and is characterized by a translocation t(12;16)(q13;p11) or, in a few percent of the cases, a t(12;22)(q13;q12), leading to the chimeric fusion product FUS-DDIT3 or EWSR1-DDIT3, respectively. 25,26 According to the literature, one-third of myxoid liposarcoma patients develop distant metastases, 18,27,28 so effective systemic therapy is needed to improve the prognosis of many patients. Previous studies reported NY-ESO-1 expression in 95-100% of myxoid liposarcomas; these results were based on sample sizes ranging from 25 to 38 cases.…”
Section: Ny-eso-1 In Mesenchymal Tumorsmentioning
confidence: 99%
“…5 Myxoid liposarcoma represents 20-30% of all liposarcomas, mostly occurs in young adults, and is characterized by a translocation t(12;16)(q13;p11) or, in a few percent of the cases, a t(12;22)(q13;q12), leading to the chimeric fusion product FUS-DDIT3 or EWSR1-DDIT3, respectively. 25,26 According to the literature, one-third of myxoid liposarcoma patients develop distant metastases, 18,27,28 so effective systemic therapy is needed to improve the prognosis of many patients. Previous studies reported NY-ESO-1 expression in 95-100% of myxoid liposarcomas; these results were based on sample sizes ranging from 25 to 38 cases.…”
Section: Ny-eso-1 In Mesenchymal Tumorsmentioning
confidence: 99%
“…CHOP transcripts are present in early blastula stage mouse embryos (Fleming et al, 1997;Fontanier-Razzaq et al, 1999), and the protein plays a role in the differentiation of osteoblasts, keratinocytes, during hematopoesis, and in the control of adipogenesis (Maytin and Habener, 1998;Tang and Lane, 2000;Pereira et al, 2004). In myxoid liposarcoma fusion proteins of CHOP and TLS (translocated in liposarcoma) result in impaired growth arrest and promote malignant transformation of cells during adipogenesis (Crozat et al, 1993;Rabbitts et al, 1993), a process that is normally controlled by Wnt signals (Ross et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The EWS-Fli1 fusion gene codes for a chimeric protein in which the amino terminal moiety of EWS, which is rich in glutamine, serine and tyrosine residues, is fused to the carboxy-terminal DNA-binding domain (ets domain) of Fli1 (Delattre et al, 1992). EWS was the ®rst member of a growing family of RNA-binding proteins, including TLS/FUS (Zinszner et al, 1994;Rabbitts et al, 1993;Crozat et al, 1993), hTAF II 68 (Bertolotti et al, 1996), the snRNP associated 69 KD protein (Hackl and Luhrmann, 1996), the bovine Pigpen protein (Alliegro and Alliegro, 1996) and Drosophila Cabeza/SARFH (Stolow and Haynes, 1995;Immanuel et al, 1995), that share distinct structural characteristics in their carboxy termini, such as an RNP motif, RGG boxes and a putative zinc-®nger domain. However, its biological functions largely remain elusive.…”
Section: Introductionmentioning
confidence: 99%